Praktyki religijne zapośredniczone medialnie jako alternatywa dla tradycyjnej religijności Polaków w czasie pandemii COVID-19 - Boguszewski, Rafał (Przegla̜d religioznawczy, 2022)
Faith and religious commitment endure as the distinguishing features of Poles when compared with other countries in Europe. However, these traits also been affected by the COVID-19 pandemic and its aftermath. Due to the limitations that accompanied Poles as the pandemic unfolded, traditional participation in religious practices could not always match the same scale and extent from before the pandemic. Consequently, some discontinued or reduced their religious involvement, while others would look for alternative forms of participation in religious practices, e.g. via radio, television or the Internet. Based on the results of quantitative research (CAWI) carried out using an online panel during the second (N = 1,072) and third wave of the pandemic (N = 1,080), the paper sets out to answer the following questions: (1) how has the religiosity of Poles changed during the pandemic?; (2) have Poles participated in religious practices via television, radio and internet?; (3) do Poles treat television, radio and online religious practices as an alternative to traditional religiosity?